KEPEMIMPINAN DAN SPIRITUALITAS: STUDI KEPEMIMPINAN KH. ABDURRAHMAN WAHID - Firdaus, Rifqi (Dahzain Nur, 2023)
Spiritual leadership is leadership that brings worldly matters to the ukhrowi (ilahiyah) dimension. Namely leadership that is able to inspire, influence through giving examples, and serve with compassion. One of the nation's leading figures and also a global Muslim intellectual, namely KH. Abdurrahman Wahid or Gus Dur. This paper aims to examine Spiritual Leadership in the perspective of KH. Abdurrahman Wahid. This research is in the nature of a literature study, in which the researcher is to obtain the results of an in-depth study related to the literature on Spiritual Leadership in the view of KH. Abdurrahman Wahid. Gus Dur has views on various issues, always assessed by Islamic universalism which prioritizes spiritual values. In his leadership he strictly forbade Islam to use violence because Islam itself is a religion of peace. However, he allowed the use of violence in certain situations, for example when pressed. But as long as the path of peace can still be taken, he forbids using violence, returning to his original law that Islam is a religion that is rahmatan lil alamin. In the political field, for Gus Dur, democracy means equal rights and status of every citizen before the law, regardless of differences in ethnicity, religion, gender and language. Gus Dur's thinking about religious tolerance does not only use the products of traditional Islamic thought, but also emphasizes the use of methodology (manhaj), legal theory (ushul fiqh), and legal principles (Qawa'id Fiqhiyah) within the framework of making a synthesis to giving birth to new ideas as an effort to respond to actual changes in society so that inter-religious conflicts can be avoided.